A framework for simultaneous training and therapy in multilateral tele-rehabilitation. (November 2016) - Sharifi, Iman; Talebi, Heidar Ali; Motaharifar, Mohammad
Abstract: The problem of designing a framework for simultaneous training and therapy in multilateral tele-rehabilitation systems is considered in this paper. The usage of robotic devices in the automation of rehabilitation procedure helps overcoming the limitation in conventional physiotherapy methods by decreasing duration of process and training sessions. The problem arises by increasing the number of robots interacting together in the tele-rehabilitation process. These robots are called "operators". In this paper, a new approach is proposed to overcome such issues. The self-intelligence between the numbers of agents working together in the multi-agent system is the key item which is used to achieve the cooperative tele-rehabilitation system. Three scenarios are proposed for implementing practical tele-rehabilitation process to satisfy the aim of simultaneous therapy and training. A simulation was launched to verify the performance of the multi-agent network; additionally, experimental study was done on the AUTWRIST robot which was designed and implemented by the authors. The simulation results approved the superiority of the proposed method in the presence of a trainee, a patient, and a therapist all together.